2015
DOI: 10.1074/jbc.m114.627463
|View full text |Cite
|
Sign up to set email alerts
|

Functional Significance of Point Mutations in Stress Chaperone Mortalin and Their Relevance to Parkinson Disease

Abstract: Background: Mortalin, an essential chaperone, is enriched in cancers; it possesses pro-proliferative and anti-apoptotic functions and has been found mutated in some Parkinson patients. Results: Mutant mortalins lack functions involved in carcinogenesis and cause increased oxidative stress; we demonstrate the factors and mechanism of their role in Parkinson disease. Conclusion: Mutations in mortalin contribute to Parkinson disease.Significance: This work contributes toward an understanding of mortalin-associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 54 publications
0
32
1
Order By: Relevance
“…Although primary breast cancer is often treated with surgery and radiation, it is the later stage when cells escape treatment due to chemoresistance and metastasis to the brain, bones, liver, and lungs. Mortalin was shown to activate telomerase, hnRNP-K, E2F1A, and PI3K/AKT proteins (23,37,38). In agreement with these known functions of mortalin, it has been detected as an upregulated protein in a variety of human tumors.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Although primary breast cancer is often treated with surgery and radiation, it is the later stage when cells escape treatment due to chemoresistance and metastasis to the brain, bones, liver, and lungs. Mortalin was shown to activate telomerase, hnRNP-K, E2F1A, and PI3K/AKT proteins (23,37,38). In agreement with these known functions of mortalin, it has been detected as an upregulated protein in a variety of human tumors.…”
Section: Discussionmentioning
confidence: 66%
“…FBS (10%) was placed in the bottom of Transwell chamber and the assembly was incubated at 37 C for 4 to 6 hours, fixed, and stained with hematoxylin and eosin (23). In vitro Matrigel invasion assays were performed using BD BioCoat Matrigel Invasion Chamber (BD Biosciences) following the manufacturer's instructions and as described previously (23).…”
Section: Migration and Invasion Assaymentioning
confidence: 99%
“…Hsp90 and its coā€chaperones regulate tau and AĪ² processing (Blair etĀ al ., 2014), and Hsp90 may specifically protect TDPā€43 from ROSā€induced aggregation (Chang etĀ al ., 2013a). The mitochondrial HSP70, also called ā€˜stressā€70ā€™ or ā€˜mortalinā€™, is implicated in PD and inĀ vitro longevity (Wadhwa etĀ al ., 2015). Lamin A mutants induce nuclear protein aggregation (Hubner etĀ al ., 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Combining the computational study with the Y2H and His-tag pull-down assays indicates that UBXN2A binds to and occupies the mortalin binding pocket within the SBD domain. As previously described (Wadhwa et al 2015). there are individual amino acids within mortalin whose mutations can dramatically change mortalin functions, including alteration in mortalin binding partners.…”
Section: Molecular Modeling Of Mortalinmentioning
confidence: 89%
“…It has been suggested that CHIP binds to mortalin and mediates proteasomal degradation of selective substrates such as p53 (Kaul et al 2007). In fact, overexpression of mortalin decreases the protein level of p53 in U2OS cells (Wadhwa et al 2015). To test whether UBXN2A can inhibit mortalin/CHIP-dependent degradation of p53 in the cytoplasm, we transiently transfected HEK293T cells with (His) 6 -CHIP E3 ubiquitin ligase Ā± GFP-empty or GFP-UBXN2A (see BMaterial and methods^section).…”
Section: Molecular Modeling Of Mortalinmentioning
confidence: 99%